2022-RA-1153-ESGO Thromboprophylaxis in surgically treated gynecological cancer patients with tinzaparin in higher than conventional prophylactic dose: preliminary results from the Song-Tin study. (20th October 2022) - Papadatou, Konstantina; Pergialiotis, Vasilios; Zachariou, Eleftherios; Rodolakis, Ioannis; Vlachos, Dimitrios-Efthymios; Haidopoulos, Dimitrios; Rodolakis, Alexandros; Thomakos, Nikolaos
Abstract : Introduction/Background: Surgeries for resection of malignant tumors are associated with a particularly high risk of venous thromboembolism (VTE). Certain abdominopelvic cancer surgeries are associated with a six to 14-fold increased risk of DVT versus surgeries for benign disease. Despite increased awareness on VTE risk, improved surgical techniques and use of primary thromboprophylaxis, the incidence of postoperative DVT remains high; it should be evaluated if extended VTE prophylaxis with more intensive doses could improve outcomes in gynecologic cancer surgery. Methodology: Song-Tin is a prospective, phase IV, observational cohort study, evaluating efficacy and safety of tinzaparin use in dose 0.4 ml, (8.000 Anti-Xa IU, OD) during hospitalization plus one month post hospital discharge, in patients with low bleeding risk, as specified in current clinical practice protocol for postoperative thromboprophylaxis, in high thrombotic risk gynecological cancer patients undergoing surgery. Results: Preliminary results from 69 surgically treated women are reported; one woman was lost to follow up and in 4 cases there were anticoagulant drug modifications (1 change drug, 2 dose increase and 1 dose decrease). ECOG status was: 0:65%, 1:22% and 2:13%; 87% were postmenopausal. Women' characteristics grouped as cancer, treatment, patient and biomarkers related presented in table 1 . Median surgery duration was 2.5 hours (Q1-Q3: 2–3 hours), median blood loss was 400 ml (Q1-Q3: 250–600 ml). Up to report time, median duration of prophylaxis with tinzaparin was 34 days (Q1-Q3: 22–38); no thrombotic events were reported (efficacy: 100%, 95%CI:0–5%). Two major bleeding events and one clinically relevant non major bleeding event occurred. None of these adjudicated as related to anticoagulant; tinzaparin dose remained the same before and after bleeding event. Conclusion: Intensive perioperative thromboprophylaxis with tinzaparin 8.000 Anti-Xa IU, OD for up to 1 month post gynecologic cancer surgery found to be effective and safe. Additional data is needed to confirm these findings.